Common pathways in dementia and diabetic retinopathy: understanding the mechanisms of diabetes-related cognitive decline. (January 2022) - Little, Karis; Llorián-Salvador, María; Scullion, Sarah; Hernández, Cristina; Simó-Servat, Olga; del Marco, Angel; Bosma, Esmeralda; Vargas-Soria, Maria; Carranza-Naval, Maria Jose; Van Bergen, Tine; Galbiati, Silvia; Viganò, Ilaria; et al.
Abstract : Type 2 diabetes (T2D) is associated with multiple comorbidities, including diabetic retinopathy (DR) and cognitive decline, and T2D patients have a significantly higher risk of developing Alzheimer's disease (AD). Both DR and AD are characterized by a number of pathological mechanisms that coalesce around the neurovascular unit, including neuroinflammation and degeneration, vascular degeneration, and glial activation. Chronic hyperglycemia and insulin resistance also play a significant role, leading to activation of pathological mechanisms such as increased oxidative stress and the accumulation of advanced glycation end-products (AGEs). Understanding these common pathways and the degree to which they occur simultaneously in the brain and retina during diabetes will provide avenues to identify T2D patients at risk of cognitive decline. Highlights: Patients with type 2 diabetes (T2D) have a significantly increased risk of cognitive decline, dementia, and Alzheimer's disease (AD). The eye as a window to the brain is an attractive concept in this field and measurable retinal changes in T2D patients may reflect linked pathology in the brain. Recent advancements have identified a number of common mechanisms in T2D and AD, which are centered around the neurovascular unit (NVU). Identification of common pathologies and molecular mechanisms involved in retinal and brain neurodegeneration may provide new therapeutic opportunities to prevent T2D-related cognitive decline and key aspects of early-stage diabetic retinopathy.